Revitalizing students activities in reading and writing in science: An investment in educational improvement - T Djudin (Pascasarjana Universitas Pendidikan Indonesia, 2018)
A literate science-information-technology people in the future cannot be prepared if based only on facts and concepts of the content areas that students acquired during school years. In a scientific literacy curriculum, reading and writing can serve as dynamic vehicles for learning science meaningfully. The explicit modeling of reading-writing- to learn needs to be integrated with teaching the curriculum at all school levels.The role expectation for teachers must change from dispensers of knowledge to developers of self-regulated learners, thinkers, and problem solvers who know to use reading and writing to learn. Our real challenge is teaching children how to read, write, and to think about science. This paper described briefly some theoretical perspectives, numerous research results, and meaningful and practical strategies on reading-writing in science. It concludes that reading-writing to learn should be developed together throughout the school years. Improving the quality of reading and writing actually improve the quality of thought and, therefore, can be regarded as an investment in educational improvement.